Antimicrobial Properties of Pliek U as Traditional Acehnese Fermented Spices - Fauzi Satria; Tri Widyawati; Taufik Sungkar (Talenta Publisher, 2024)
The high prevalence of antimicrobial resistance globally has increased the burden of disease. The phenomenon demands urgency to explore new antimicrobial drugs, one of which is sourced from natural ingredient, spices. Pliek U, as one of the spices traditionally processed by Acehnese, has attracted researchers to explore its potential source for antimicrobial substances. The objective of this literature review is to explore the characteristic, production, chemical composition, and antimicrobial mechanism of Pliek U. A literature search was carried out on PubMed, Science Direct, Springer Link, and Google Scholar using the keywords